Strengthening Green Tourism Branding for Tourism MSMEs in Pematang Johar Village, Deli Serdang - Budi Febriani; Pristiyono; Rika Syahmewah; Marlina Siregar; Bayu Eko Broto; Syahrizal Efendi Lubis (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Pematang Johar Village in Deli Serdang Regency has nature-based and rice field tourism potential that can be developed as a community-based green tourism destination. However, tourism MSME actors in the village still face challenges in building brand identity, formulating promotional messages, communicating environmentally friendly values, and using digital media consistently. This community service activity aims to strengthen green tourism branding for tourism MSME actors through training, mentoring, product storytelling practices, and simple digital promotional content development. The implementation method uses a participatory approach consisting of preliminary observation, partner coordination, problem mapping, green tourism branding training, product storytelling practice, digital content assistance, and activity evaluation. The target participants are tourism MSME actors, tourism managers, village youth, and community members supporting tourism activities in Pematang Johar Village. The outputs of the activity include participants' understanding of green tourism branding, MSME product storytelling templates, examples of digital promotional messages, green tourism campaign drafts, and activity documentation. The expected result of this program is the improvement of MSME actors' ability to package tourism products and services in a more attractive, environmentally friendly, and locally distinctive manner. This activity indicates that simple, practical, and locally based branding assistance can be an effective strategy to strengthen the competitiveness of tourism MSMEs in rural destinations.